Determination of trace amount of cadmium using dispersive liquid-liquid microextraction-slotted quartz tube-flame atomic absorption spectrometry - Firat, Merve; Bakirdere, Sezgin; Findikoglu, Maral Selin; Kafa, Emine Betul; Yazici, Elif; Yolcu, Melda; Buyukpinar, Cagdas; Chormey, Dotse Selali; Sel, Sabriye; Turak, Fatma (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
This study was performed to develop a sensitive analytical method for the determination of cadmium by slotted quartz tube-flame atomic absorption spectrometry (SQT-FAAS) after dispersive liquid-liquid microextraction (DLLME). The parameters affecting the cadmium complex formation and its extraction output were optimized to obtain high extraction efficiency. These included the pH and amount of the buffer solution, and the concentration of the ligand. The DLLME method was comprehensively optimized based on the type and amount of extraction solvent, dispersive solvent and salt The type and period of mixing needed for a more effective extraction was also investigated. In order to further improve the sensitivity for the determination of cadmium, the flame atomic absorption spectrometry was fitted with a slotted quartz tube to increase the residence time of cadmium atoms in the pathway of incident light from a hollow cathode lamp. The limits of detection and quantitation (LOD and LOQ) for the FAAS were found to be 42 and 140 mu g L-1, respectively. Under the optimum conditions, LOD and LOQ of the FAAS after DLLME were calculated as 1.3 and 4.4 mu g L-1, respectively. Combining both optimized parameters of the DLLME and SQT-FAAS gave 0.5 and 1.5 mu g L-1 as LOD and LOQ, respectively. Accuracy of the method was also checked using a wastewater certified reference material (EU-L-2), and the result was in good agreement with the certified value. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Cadmium; Microextraction; DLLME; SQT; FAAS; CLOUD-POINT EXTRACTION; ONLINE PRECONCENTRATION; SENSITIVE DETERMINATION; LEAD; COPPER; SAMPLES; NICKEL; PB; CD; BISMUTH; Spectroscopy